Enhancing Geodetic Control Points through GNSS and CORS Integration: A Case Study of Ibadan, Nigeria - Oyeyode Ajiboye Oyesiji; T.O. IDOWU; D.N. OLAYINKA-DOSUMU; I.U. NZELIBE (African Journal on Land Policy and Geospatial Sciences)
Context and background: